Carnosine Protects against Cerebral Ischemic Injury by Inhibiting Matrix-Metalloproteinases - Kim, Eun-Hye (Int J Mol Sci, 2021)
Stroke is one of the leading causes of death and disability worldwide. However, treatment options for ischemic stroke remain limited. Matrix-metalloproteinases (MMPs) contribute to brain damage during ischemic strokes by disrupting the blood-brain barrier (BBB) and causing brain edemas. Carnosine, an endogenous dipeptide, was found by us and others to be protective against ischemic brain injury. In this study, we investigated whether carnosine influences MMP activity. Brain MMP levels and activity were measured by gelatin zymography after permanent occlusion of the middle cerebral artery (pMCAO) in rats and in vitro enzyme assays. Carnosine significantly reduced infarct volume and edema. Gelatin zymography and in vitro enzyme assays showed that carnosine inhibited brain MMPs. We showed that carnosine inhibited both MMP-2 and MMP-9 activity by chelating zinc. Carnosine also reduced the ischemia-mediated degradation of the tight junction proteins that comprise the BBB. In summary, our findings show that carnosine inhibits MMP activity by chelating zinc, an essential MMP co-factor, resulting in the reduction of edema and brain injury. We believe that our findings shed new light on the neuroprotective mechanism of carnosine against ischemic brain damage.